2012
DOI: 10.1016/j.jcis.2011.12.072
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial concentrations of chloride and bromide in zwitterionic micelles with opposite dipoles: Experimental determination by chemical trapping and a theoretical description

Abstract: Interfacial concentrations of chloride and bromide ions, with Li(+), Na(+), K(+), Rb(+), Cs(+), trimethylammonium (TMA(+)), Ca(2+), and Mg(2+) as counterions, were determined by chemical trapping in micelles formed by two zwitterionic surfactants, namely N-hexadecyl-N,N-dimethyl-3-ammonio-1-propanesulfonate (HPS) and hexadecylphosphorylcholine (HDPC) micelles. Appropriate standard curves for the chemical trapping method were obtained by measuring the product yields of chloride and bromide salts with 2,4,6-trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In the conductometric studies of cationic surfactants in the presence of cell suspensions, the relevant inflection points observed were at amphiphile concentrations lower than cmc, and the microbiological and FTIR studies also confirmed the action of the surfactant monomers on the cells. , In the case of sulfobetaine surfactants, the inflection points are only observed at micelle formation. Zwitterionic micelles have different and peculiar properties compared to the ones of charged micelles, particularly on their ionic structure and on their ion-uptake peculiar capability. In the recent literature the authors postulated many different models to interpret these peculiarities. Souza and co-workers treated the theme of specific ion association on zwitterionic micelles, reported as “chameleon-like” behavior. In previous works regarding micellar effects on reactivity and on micellar structure of zwitterionic surfactants, it has emerged that micelles of zwitterionic sulfobetaines have a “cationic-like” behavior , that is due to the charge distribution in the micellar structures.…”
Section: Resultsmentioning
confidence: 99%
“…In the conductometric studies of cationic surfactants in the presence of cell suspensions, the relevant inflection points observed were at amphiphile concentrations lower than cmc, and the microbiological and FTIR studies also confirmed the action of the surfactant monomers on the cells. , In the case of sulfobetaine surfactants, the inflection points are only observed at micelle formation. Zwitterionic micelles have different and peculiar properties compared to the ones of charged micelles, particularly on their ionic structure and on their ion-uptake peculiar capability. In the recent literature the authors postulated many different models to interpret these peculiarities. Souza and co-workers treated the theme of specific ion association on zwitterionic micelles, reported as “chameleon-like” behavior. In previous works regarding micellar effects on reactivity and on micellar structure of zwitterionic surfactants, it has emerged that micelles of zwitterionic sulfobetaines have a “cationic-like” behavior , that is due to the charge distribution in the micellar structures.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the adsorption properties of sulfobetaine micelles depend on the structure of the zwitterionic surfactants, namely, C n H 2 n +1 N + R 2 (CH 2 ) m SO 3 – , where for R = CH 3 they are denoted simply as SB m - n . The effects of the linear alkyl tail length ( n = 10–16), the size of the methylene tether group ( m = 2–4), and the N -alkyl group length (R = C k H 2 k +1 with k = 1–4) have been investigated. ,, , In addition, the effects of substituents in the tether group, the nature of the positively charged group in the zwitterionic headgroup, and the dipole orientation of the headgroup upon the properties of sulfobetaine micelles were also explored. ,, Regarding the dependence on the electrolyte, for instance, the anion adsorption at SB3-14 decreases as ClO 4 – > I – > Br – > Cl – > F – , , which follows a Hofmeister-type series and may be related to the softness of the anions and their hydration energies. These observations are intriguing because a proposed idealized structural model of (near-)­spherical micelle formed by (quasi-)­linear monomeric surfactants, ∧∧∧∧∧⊕∧⊖, would provide a negative surface, which would not be an environment to adsorb anions.…”
Section: Introductionmentioning
confidence: 99%
“…8,11,[14][15][16]22 In addition, the effects of substituents in the tether group, the nature of the positively charged group in the zwitterionic headgroup, and the dipole orientation of the headgroup upon the properties of sulfobetaine micelles were also explored. 20,21,30 Regarding the dependence on the electrolyte, for instance, the anion adsorption at SB3-14 decreases as ClO 4 − > I − > Br − > Cl − > F − , 14,19 which follows a Hofmeister-type series 31−33 and may be related to the softness of the anions and their hydration energies. These observations are intriguing because a proposed idealized structural model 7−13 of (near-)spherical micelle formed by (quasi-)linear monomeric surfactants, ∧∧∧∧∧⊕∧⊖, would provide a negative surface, which would not be an environment to adsorb anions.…”
mentioning
confidence: 99%
“…Salt effects upon zwitterionic micelles are less pronounced than those observed in cationic or anionic micelles ,, although smaller SIEs are still present in these systems. As expected, bromide showed higher interfacial affinity than chloride, but both anions did not disturb the DPS micelle.…”
Section: Discussionmentioning
confidence: 97%
“…Zwitterionic micelles are formally neutral but can selectively adsorb ions at the interface. Several experimental techniques have been used to evaluate specific anion adsorption at the interface of sulfobetaine micelles, a well-known zwitterionic system, and the degree of anion adsorption is usually associated with its hydration free energy. , The studied anions usually belong in the Hofmeister series, and the degree of adsorption follows this series. Thus, perchlorate anions adsorb in the interface to a larger degree than bromide, as seen by zeta potential measurements, but still does not produces changes in aggregation number or micellar shape. , …”
Section: Introductionmentioning
confidence: 99%